ANALISIS PENGENDALIAN KUALITAS PRODUK BATIK TULIS DENGANMETODE STATISTICAL QUALITY CONTROL PADA UMKM A - Alif Hendradi (2023)
Competition in the business world, both in the fields of trade, industry and manufacturing, is currently very tight. Quality control is an important thing that must be implemented in the production process to give a sense of trust to consumers. To be able to survive in the competition"In business, maintaining consistent product quality must be carried out by the textile industry. UMKM A is an industry engaged in the production of written batik. The purpose of this research is to identify the most dominant type of disability, to find out the factors that cause defects, to model the relationship between factors that cause defects and defects. as well as submit suggestions related to improving product quality control with methodsStatistical Quality Control (SQC), PDCA approach (plan,do,check,action) as well as analysis usingseven tools and statistical tests of multiple linear regression which were processed using SPSS. The results of the research showdefect dominant in production at UMKM A, namely atdefect total uneven color 44%. The factors that cause itdefect namely the human factor which has a greater influence than other factors and also obtained a multiple linear regression model which has the equation Y = 1.576 + 0.189 X1 + 0.244 X2 + 0.313 X3 + 0.229 X4 + e with a value of Rsquare . 0.714. This can be minimized by training the workforce, on the production process, making SOPs, carrying out checksheets on production and making standard defects tests with test equipmentgreyscale which revised from SNI-08-0288-1989